Comparison of Shear Bond Strength of Three Luting Materials Used in Band and Loop Space Maintainer Cementation: An In Vitro Study - Sara Muhannad Zaidan; Reem Atta Rafeeq (Wolters Kluwer Medknow Publications, 2022)
Introduction: Aim of this study is to compare shear bond strength of different luting materials used in fixed space maintainer cementation. Methods: Thirty intact extracted human third molars randomly divided into three equal groups: group A: RelyX luting 2 (resin modified glass ionomer); group B: TOTALCEM (self-adhesive resin cement/ dual cure); group C: Transbond plus (compomer). After bonding procedures, the samples were kept in distilled water at 37°C for 24 hours prior to the shear bond strength test. Data were analyzed blindly by one-way ANOVA test and the Tukey post hoc test using R software. Results: There were statistically significant differences between the three luting materials (P  <  0.001). Conclusion: TOTALCEM showed significantly higher shear bond strength than RelyX luting 2 and Transbond plus. With respect to limitations of in vitro studies, long-term clinical studies required.